(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing is Internet-based computing and the next stage in the evolution of the internet. The uses of the cloud attract different industries in the recent decade, but this brings security challenges against attacks from insider or outsider, human or bot. Many researchers are working continuously to resolve the issues by introducing policies, algorithms for accessing and storage of client data. This paper gives a detailed survey on IAAS security issues. A virtual machine should be secured to handle data and maintain privacy. Methods proposed by various scholars are explained which directly or indirectly enhance the security of the cloud. Tenant-based measures were also in the solutions to various issues. Paper has listed some of the trust techniques developed by researchers for identifying any malicious machine.